Sex and control : venereal disease, colonial physicians, and Indigenous agency in German colonialism, 1884-1914 - Walther, Daniel Joseph, 1965- (Monographs in German history, 2015)
""The author...explains venereal diseases in the former German Imperial colonies in Africa, the Pacific, and Kiautschou/China as an epidemiological, but most of all, cultural and social phenomenon....A detailed study on venereal diseases and their political, social, cultural, and of course medical impact was missing so far. Walther adds it to colonial historiography."" · Wolfgang U. Eckart, University of Heidelberg ""...this is a thoroughly researched and original work which makes a fine contribution to its field. There has been a lot of interest recently in histories of empire and German.